Penerapan Internet of Things Untuk Rancang Bangun Pengukuran Tingkat Kebisingan pada Sarana Perkeretaapian - Teguh Arifianto; Santi Triwijaya; Ditya Nurma Paulina; Sunardi; Andrew Joewono; Joewono Prasetijo (Lembaga Pengembangan Kinerja Dosen, 2023)
Noise is an unexpected sound from business or activity at a certain level and time, which can cause reduced comfort. The causes of noise can be grouped based on the sound and noise spectrums. However, in general, noise sources come from traffic, industrial, aeroplane, and train activities. When the wheels scuff up against the rail surface, a train operates, producing noise. In this research, a design was created to monitor the noise level produced by railway facilities. This system is made using main components such as arduino uno, DFR0034 sound sensor, SIM800L, and other supporting components. The system is designed to be able to monitor and display data on the noise values that occur. The system is designed based on the internet of things so that it can display data automatically on the computer. Data can be accessed using thingspeak via SIM800L as an internet source, making it easy to observe and measure noise. This design testing was carried out using light rail transit trains, inspection trains, and lorries. Noise levels in trains range from 70 dB to 80 dB. If more than 80 dB is detected, the cause of the noise can be checked to maintain the comfort and safety of passengers and avoid more serious damage if damage is found to the facilities.